2019
DOI: 10.1158/1535-7163.mct-18-0456
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MERTK Promotes Suppression of Tumor Growth in BRAF Mutant and BRAF Wild-Type Melanoma

Abstract: Molecularly-targeted agents have improved outcomes for a subset of patients with BRAF-mutated melanoma, but treatment of resistant and BRAF wild-type tumors remains a challenge. The MERTK receptor tyrosine kinase is aberrantly expressed in melanoma and can contribute to oncogenic phenotypes. Here we report the effect of treatment with a MERTK-selective small molecule inhibitor, UNC2025, in preclinical models of melanoma. In melanoma cell lines, treatment with UNC2025 potently inhibited phosphorylation of MERTK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
(89 reference statements)
1
27
0
Order By: Relevance
“…TAM receptor family member mediated regulation of the T cell response within the tumor is an active area of clinical and pre-clinical research (Myers et al, 2019;Wu et al, 2018a). Mertk specific inhibition has been shown to suppress tumor growth in murine solid tumor models (Cook et al, 2013;Sinik et al, 2018;Wu et al, 2018b). Additionally, suppression of TAM receptor signaling has been shown to increase the response to anti-PD-1 therapy in a murine tumor model, suggesting that it is mediated by a mechanism other than PD-1 signaling (Kasikara et al, 2019), as we have observed in our autoimmune models.…”
Section: Mertk Regulates T Cell Arrest In a Solid Tumorsupporting
confidence: 73%
“…TAM receptor family member mediated regulation of the T cell response within the tumor is an active area of clinical and pre-clinical research (Myers et al, 2019;Wu et al, 2018a). Mertk specific inhibition has been shown to suppress tumor growth in murine solid tumor models (Cook et al, 2013;Sinik et al, 2018;Wu et al, 2018b). Additionally, suppression of TAM receptor signaling has been shown to increase the response to anti-PD-1 therapy in a murine tumor model, suggesting that it is mediated by a mechanism other than PD-1 signaling (Kasikara et al, 2019), as we have observed in our autoimmune models.…”
Section: Mertk Regulates T Cell Arrest In a Solid Tumorsupporting
confidence: 73%
“…Inhibition of MERTK has been found to promote innate tumor immunity by decreasing M2‐macrophage polarization and efferocytosis (removal of dead cells by phagocytes) (Boada‐Romero et al., 2020; Sinik et al., 2019). This mechanism offers the opportunity for targeted immunotherapy to treat cancer; however, the ocular expression of MERTK increases the difficulty for developing a targeted drug due to toxicity concerns.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Only a subset of patients benefits from MEK inhibitors used as single agents, because they only produce cytostatic effects rather than cytotoxic effects, in NRAS mutant melanoma cells (13). MEK inhibitors are also associated with primary and acquired resistance as well as frequent toxicity-related adverse events (14,15). However, MEK inhibitors could deliver promising therapies when combined with inhibitors of other signaling mechanisms (12,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…MEK inhibitors are also associated with primary and acquired resistance as well as frequent toxicity-related adverse events (14,15). However, MEK inhibitors could deliver promising therapies when combined with inhibitors of other signaling mechanisms (12,(15)(16)(17). Currently, the MEK inhibitor FCN-159, which has 10-fold higher selectivity against activated MEK1/2 compared to trametinib, is being investigated as a single agent in a phase I clinical trial (NCT03932253).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation